2023
DOI: 10.1101/2023.02.14.528436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the ageing methylome in the model insect,Nasonia vitripennis

Abstract: Epigenetic clocks in humans are argued to be a measure of true biological age based on the DNA methylation status of selected sites in the genome. Here we discover for the first time, an epigenetic clock in a model insect system, Nasonia vitripennis. By leveraging the power of an insect model, future studies will be able to research the biology underpinning epigenetic clocks and how influenced epigenetic clocks are by ageing interventions.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(104 reference statements)
1
2
0
Order By: Relevance
“…Consistent with the role of DNAme in lifespan regulation in invertebrates, recent studies have shown that the patterns of this epigenetic mark are influenced by age in the parasitoid wasp Nasonia vitripennis [65] and the water flea Daphnia magna [66]. Our functional analyses revealed that RG108 significantly affected DNAme in the CG context, but not in the non-CG context.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the role of DNAme in lifespan regulation in invertebrates, recent studies have shown that the patterns of this epigenetic mark are influenced by age in the parasitoid wasp Nasonia vitripennis [65] and the water flea Daphnia magna [66]. Our functional analyses revealed that RG108 significantly affected DNAme in the CG context, but not in the non-CG context.…”
Section: Discussionsupporting
confidence: 87%
“…The direction of changes in DNA methylation at specific positions has been used to predict the chronological age of organisms with accuracy ( Horvath 2013 ; Horvath and Raj 2018 ). Epigenetic drift due to aging is observed in diverse species such as mammals, birds, other vertebrates, and some invertebrates ( Fairfield et al 2021 ; Sun et al 2021 ; Mayne et al 2022 ; Brink et al 2023 ). If epigenomic studies of populations include individuals of different ages, epigenetic drift can present itself as variation within or between populations, independent of genetic variation.…”
Section: Sources Of Epigenetic Variationmentioning
confidence: 99%
“…The most commonly used invertebrate aging models, D. melanogaster and C. elegans have no or very limited cytosine methylation [56,57]. However, cytosine methylation is found in many invertebrate animals, but methylation clocks have not been tested extensively in these species (but see [58][59][60]). If a ground zero model-for cytosine methylation or another molecular markerdoes apply to species other than mammals, then the "ground zero" time point might serve as the common starting point to determine age and allow for the comparison of equivalent age data between species.…”
Section: Measuring Lifespan and Agementioning
confidence: 99%